Is there any association between type of dietary fat and quality of life in hemodialysis patients? A cross-sectional study - Navab, Fatemeh; Foshati, Sahar; Vajdi, Mahdi; Askari, Gholamreza; Moeinzadeh, Firouzeh; Heshamtipour, Houri; Mirzaeian, Soheila; Rouhani, Mohammad Hossein (Frontiers in Nutrition, 2024)
Background: Hemodialysis (HD) patients have a low quality of life (QOL), and dietary intakes may impact both somatic and psychosocial aspects of QOL. Nevertheless, the relationship between QOL and different dietary fats has not yet been evaluated.The purpose of this study was to assess the association between QOL and the types/quantities of dietary fats intake in HD patients.In this multi-center cross-sectional study, 251 adult patients under dialysis for at least three months were included. Participants' dietary intakes were collected using a validated 168-item semiquantitative FFQ during the past year. Moreover, to assess QOL, Kidney Disease Quality of Life Short Form (KDQOL-SF 1/3) was used. The linear regression between QOL and different types of dietary fats was conducted. P<0.05 was statistically significant.Results: Overall, 66 women and 185 men participated in our study. Regression analysis adjusted for total calorie intake showed that there was a negative association between QOL and total fat (95% CI: -0.187, -0.043), SFA (95% CI: -0.688, -0.143), MUFA (95% CI: -0.389, -0.065) and PUFA (95% CI: -0.401, -0.056) when types of dietary fats were individually included to the regression analysis. When all types of dietary fats were simultaneously entered into the analysis, the association between QOL and MUFA (95% CI: -0.243, 1.031) and PUFA (95% CI: -1.159, 0.084) were attenuated. The regression coefficient for SFA remained significant (95% CI: -0.968, -0.138). Also, there was a marginally significant association between SFA and the risk of low QOL was observed when all types of dietary fats were simultaneously entered into the analysis (OR=1.051, 95% CI: 0.998-1.104).Our investigation found a negative association between SFA consumption and QOL among different types of dietary fats. Furthermore, SFA mediated the relationship between QOL, MUFA, PUFA, and total fat. So, modification of dietary fat intake could enhance QOL in HD patients.